Patients with Tinnitus: Their Perspective on Sound Generators - Bérangère Villatte; Charlotte Bigras; Philippe Fournier; Elizabeth Fitzpatrick; Sylvie Hébert (Noise and Health, 2025)
Objective: Sound therapy (ST) is a well-known treatment option for tinnitus patients. However, patient perspectives on this option remain scarce. This study investigated the perspectives of first-time sound generator users on ST for chronic tinnitus, focusing on their perceptions of the sound generators and the effects on tinnitus. Methods: The subjects were 29 adult patients with chronic tinnitus who received ST using sound generators for the first time. In the 3-week ST trial, In the 3-week ST trial, hearing aids with built-in sound generators built idelivered broadband noise at a low and individualized sound level. Semistructured interviews were conducted 1 month after the ST trial. Using an interpretive description approach, themes were captured qualitatively to describe patients’ subjective experience of the ST. Results: After performing inductive coding on the dataset, five main themes emerged: (1) effects while wearing the generators; (2) effects after removing the generators; (3) perception of the generated noise; (4) untargeted effects; and (5) purchasing sound generators. Each theme was further subdivided into one to three subthemes. Conclusions: The study highlighted uncertainties regarding the overall perceived benefits of short-term ST, with results influenced by initial noise hypersensitivity, hearing loss, and noise appreciation. Future research should examine the benefits of ST after controlling for these variables and compare the effects of different types of tailored sound on each dimension of tinnitus. Understanding how noise physiologically modulates tinnitus both during and after exposure is crucial to better counsel patients on what to expect.